(untitled) (The Pakistan Development Review, 2000)
Agriculture is the mainstay of the most developing countries, which supplies food and employment to the majority of the population. Because of the dominance of the agricultural sector, a sufficient supply of domestic food is indispensable to support stable socio-economic and political systems in these countries. To attain a sustained growth of agricultural productivity, sufficient investment in the agricultural sector is crucial, particularly in the initial stages of economic development. This increases agricultural production and as a result, there is a shift in (human) resources from the agricultural sector to the industrial and services sectors. According to Duranton (1998), in order to transform from agricultural sector to industrial sector a significant increase in the agricultural sector productivity is necessary. On the demand-side, the growth in agricultural production increases agricultural income which leads to increase in the demand for industrial products; whereas on the supplyside, the increase in the agricultural productivity shifts human resources from the agricultural to the industrial sector [Jorgenson (1967)].